SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KOMITMEN KERJA GURU PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH KEJURUAN NEGERI 5 MUARO JAMBI - Hendri; Mahmud MY; Jaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the principal’s supervision in improving the work commitment of Islamic Education teachers at SMK Negeri 5 Muaro Jambi. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The findings show that the principal’s supervision is carried out through structured supervision planning, classroom supervision activities, feedback provision, and continuous professional guidance. The supervision conducted by the principal has been proven to enhance the work commitment of Islamic Education teachers, as reflected in improved responsibility in lesson planning, discipline, teaching quality, and motivation to engage in professional development. Supporting factors include school support, effective communication, and teachers’ willingness to improve, while inhibiting factors involve limited time, administrative workload, and suboptimal facilities. This study concludes that effective principal supervision plays an important role in strengthening the work commitment of Islamic Education teachers in the school.